Le glacier de l’Eqe (Eqip sermia). Mouvement et variations du front (1959). - Bauer, A. (Meddelelser om Grønland, 1968)
The front and the flow of Eqip sermia have been determined in July 1959. The accuracy of the geodetic measurements is given. The successive positions of the front from 1912 to 1964 show that the glacier presented a growth about in 1920, and has been retreating since then.